2022
DOI: 10.1002/cam4.5149
|View full text |Cite
|
Sign up to set email alerts
|

Quality of integrated female oncofertility care is suboptimal: A patient‐reported measurement

Abstract: Background Clinical practice guidelines recommend to inform female cancer patients about their infertility risks due to cancer treatment. Unfortunately, it seems that guideline adherence is suboptimal. In order to improve quality of integrated female oncofertility care, a systematic assessment of current practice is necessary. Methods A multicenter cross‐sectional survey study in which a set of systematically developed quality indicators was processed, was conducted amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…Accordingly, very few women completed cryopreservation, which tripled after 2013 due to the introduction of oocyte cryopreservation as a non-experimental option, and some even completed OTC at that time. Similar low cryopreservation rates of women treated in these times have been described previously [62,63], and fertility-related counseling in female cancer patients continues to be suboptimal [64]. Additional research in more recently treated AYA women is needed.…”
Section: Female Survivorsmentioning
confidence: 73%
“…Accordingly, very few women completed cryopreservation, which tripled after 2013 due to the introduction of oocyte cryopreservation as a non-experimental option, and some even completed OTC at that time. Similar low cryopreservation rates of women treated in these times have been described previously [62,63], and fertility-related counseling in female cancer patients continues to be suboptimal [64]. Additional research in more recently treated AYA women is needed.…”
Section: Female Survivorsmentioning
confidence: 73%
“…In a few studies, patients indicated that initiating the discussion was influenced by interpretation of social status (i.e., married, single, existing children) and that unwarranted assumptions are made about fertility desires and plans [24,27,33]. Also, (higher) age is seen as a factor for not offering FP services [9,39,52,54]. Studies, however, show that assumptions based on socio-demographic factors are not reliable determinants about a patient's fertility desires and needs [24,32,64].…”
Section: Starting a Conversation About Potential Fertility Declinementioning
confidence: 99%